Phoenix dactylifera seed-derived biochar as a sustainable and environmentally feed supplement in camel: impacts gas production, methane emissions, nutrient degradability and fermentation parameters, performance predictions - Hesham S. Ghazzawy; Nashi K. Alqahtani; Nashi K. Alqahtani; Nashi K. Alqahtani; Abdullah Sheikh; Mohamed Shawky El Sayed; Roshmon Thomas Mathew; Hassan M. Ali-Dinar; Ehab El-Haroun; Mohamed M. A. Abd-Elkarim; Sameh A. Abdelnour; Ali S. A. Saleem (Frontiers in Veterinary Science)
IntroductionClimate change poses a significant environmental challenge to all living organisms. Camels exhibit notable resilience to these changes. Concurrently, the date palm (Phoenix dactylifera), a widely cultivated plant in tropical and subtropical regions, generates substantial seed waste. Valorizing Phoenix dactylifera seed-derived biochar (PSB) to enhance feed supplements and mitigate environmental impacts presents a potentially sustainable and eco-friendly solution. This study investigated the potential of date palm seed-derived biochar as a sustainable feed additive for dromedary camels to reduce methane (CH₄) emissions and improve gas production, nutrient degradability, fermentation parameters, and performance predictions using in vitro models.MethodsThe PSB was synthesized and stored at 4°C until use. Ruminal fluids were collected from growing camels (24-36 months old) at the nutrition laboratory and subsequently incubated at 37°C. The basal diet was supplemented with PSB at 0, 1, 2, and 4%, and the resulting data were analyzed using polynomial analysis. Gas production, methane emissions, nutrient degradability, fermentation parameters, and performance predictions were assessed.ResultsAt 6, 12, and 36 hours of incubation, all levels of PSB biochar supplementation resulted in a significant linear increase in gas production (p < 0.05). The inclusion of PSB significantly reduced CH₄ emissions in a quadratic manner (p < 0.001). The lowest reduction in CH₄ production was observed at the 1% and 2% PSB inclusion levels, with a greater reduction at the 4% level (quadratic effect; p < 0.001). A significant quadratic increase in TVFA production was observed with increasing PSB inclusion levels during the in vitro fermentation of camel diets (quadratic effect; p < 0.01). Furthermore, pH values significantly decreased with biochar supplementation, exhibiting a linear trend with the lowest values at the 4% level, followed by 2% and 1% (linear effect; p < 0.01). Short-chain fatty acid (SCFA) production was improved by the addition of PSB compared to the control diet in camels (quadratic effect; p < 0.01). The inclusion of 1% or 2% PSB quadratically improved organic matter digestibility (%), metabolizable energy (DM), and net energy for lactation (NEL) in camels. Microbial crude protein (MCP) and purine derivatives (PD) were not significantly affected by PSB supplementation (p > 0.05).ConclusionIn summary, the addition of PSB enhanced gas production, nutrient degradability, fermentation parameters, and performance predictions, while concurrently mitigating methane emissions in vitro. This study underscores the potential of utilizing PSB as a valuable feed supplement and a sustainable feed additive for dromedary camels in extensive production systems.